Effects of gender of dairy or beef cattle and the number of pair of permanent incisors on carcass traits - Kunya Tuntivisoottikul; Rutcharin Limsupavanich (My University, 2018)
Effects of group of cattle (gender of dairy or beef cattle) and number of pair of permanent incisors (0-4 pairs) on carcass traits were investigated. Data collected from 2,059 carcasses were obtained from beef cattle cooperative in 2016. Carcass traits included slaughter weight (wt.), hot carcass wt., percentage of hot or chilled carcass wt., chilling loss, skin wt., and marbling score. Factors included group of cattle and number of pair of permanent incisors observed in each cattle group, while slaughter wt. was a co-variable in the statistical model. Descriptive statistics were used to analyze marbling score. Results showed that group of cattle affected slaughter wt., hot carcass wt., percentage of hot or chilled carcass wt., skin wt. (P<0.0001), and chilling loss (P<0.05). Number of pair of permanent incisors within each cattle group affected all carcass traits (p<0.05), except chilling loss (p>0.05). Female and male beef cattle in all ages had higher hot carcass wt. and percentage of hot or chilled carcass wt. than female and male dairy cattle. The highest marbling score of 5 was found in female and male beef and female dairy cattle with 4 pairs of permanent incisors. However, majority of cattle had marbling score 2.
Keywords: Marbled meat; Carcass weight; Beef Cattle; Meat and Animal Product Quality